PERAN PUSAT PELAYANAN TERPADU PEMBERDAYAAN PEREMPUAN DAN ANAK (P2TP2A) KOTA PEKANBARU DALAM PENANGANAN KEKERASAN DALAM RUMAH TANGGA DI KOTA PEKANBARU TAHUN 2016-2017 - Zulfadly "; Wan Asrida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Domestic violence or more commonly referred to as domestic violence is a social problem, which can hamper national development programs, which should be felt equally between men and women without discrimination. This attracted the attention of researchers with the title "The Role of Integrated Service Centers for Women and Children Empowerment (P2TP2A) in Pekanbaru City in Handling Domestic Violence in Pekanbaru City in 2016-2017", The purpose of this study was to determine the role of Pekanbaru P2TP2A in handling domestic violence cases in Pekanbaru City 2016-2017.     This study uses a qualitative research approach. While this type of research is descriptive. The types of data used are primary and secondary data and supported by the results of interviews and other supporting documents for this study, the data will be analyzed in a qualitative descriptive way. The theoretical foundation used is role theory and coordination theory                Based on the analysis of the data obtained, the conclusion is the role of the Integrated Service Center for Women and Children Protection (P2TP2A) in Pekanbaru City in handling cases of domestic violence where the role of P2TP2A in handling domestic violence is still not optimal, namely; Facilitating the outreach of victims handling community complaints, Organizing temporary shelter services for victims, and Facilitating the return of victims to their home areas and family environment, this is due to budget constraints, human resources owned by Pekanbaru P2TP2A and still lack of cooperative attitude from reporters victims so that the process of handling cases of violence has not been optimal. In addition, P2TP2A coordinates with relevant agencies; police, Health Service / Puskesmas, Social Service / RPTC Riau Province, and Education Office. Keywords: Coordination, Facilitation, Mediation, Partnership